Editorial (American Journal of Islam and Society, 2006)
When the tribes of Makkah decided to rebuild the Ka`bah, they workedtogether well until it was time to return the Black Stone to its corner. Eachclan wanted the honor of this task, and tensions ran high for four or fivedays due to the stalemate over who would have the honor of lifting theBlack Stone so that it could be returned to its proper place. With battlepreparations underway, one man decided to try and avert a fight by suggestinga rather unorthodox idea: The first man to walk into the area wouldbe appointed to arbitrate the dispute. Everyone agreed and began to wait.And so it was that Muhammad ibn Abdullah was the first to enter. Seeingthis, the men reached a spontaneous agreement that he was indeed the bestone to resolve this crisis, for he was known to all of them as a person oftruth. Muhammad analyzed the situation and then asked for a cloak.Telling them to spread it out on the ground, he asked each clan to take holdof a corner. After placing the Black Stone in the middle, he asked them toraise the cloak so that he could place the Black Stone back in its properplace.This was Muhammad ibn Abdullah, a man of truth, integrity, and peace;a man who, according to Muslim belief, later became the last Prophet ofGod. Muhammad ibn Abdullah: about whom Muslims say “salla Allahu`alayhi wasallam” (May the peace and blessings of God be upon him) eachtime his name is mentioned; about whom they ask God to bless, just as Hehad blessed Abraham his family, at each of the five daily prayers; aboutwhom it is said that God say ten prayers on anyone who says one prayer onhim. In contrast with the 1,400 year old Muslim tradition of reverencetoward Muhammad ibn Abdullah (pbuh), (indeed toward all of theprophets), a European tradition gradually sprung up dedicated to depictingMuhammad ibn Abdullah as an evil “magician” out to destroy Christendom.Pope Innocent III (1161-1216) even called him the Anti-Christ. During themedieval era, the bogey used to frighten naughty children into obediencewas “Mahomet.”This negative image of Prophet Muhammad (pbuh) remains deeplyingrained in the European psyche (and, by extension, the colonized NewWorld, now known as “the West”). Indeed, it is so deeply ingrained that ...